Pengaruh Harga Paket Umroh, Tingkat Inflasi, dan Kurs Rupiah Pada Dollar Terhadap Permintaan Jasa Umroh di Surabaya Periode 2011-2013 - Masruhatul Abadiyah; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
There is an interesting phenomena recently that the demand of umroh serviceincreases significantly. This increase is caused by the waiting list for Hajj departure which has to wait for a few years later to take place. This makes the society to take an alternative umroh first which doesn't have to wait for too long.This research aims to find out the effect of umroh package price, inflation rate and rupiah exchange for dollar towards Surabaya umroh service demand during 2011-2013 period. This research uses quantitative approach method and multiple linear regression analysis.The result shows that the umroh packageprice, inflation rate, and rupiah exchange for dollar variables simultaneously do not have significant effect towards Surabaya umroh service demand during 2011-2013 period. For addition, simultaneously the umroh package price, inflation rate, and exchange rate variables give negative effect towards Surabaya umroh service demand during 2011-2013 period.Umroh service bureaus especially those which reside in Surabaya need to maintain and improve their performances well in order to provide satisfaction and loyalty of the jamaah to increase the demand of umroh service. REFERENCES Fakhrudin. 2008. Manasik Haji dan Umroh. Surabaya : PT Pustaka Tiga.Gujarati, Damodar. 2003. Basic Econometrica. New York : The Mc.Graw Hill Company, inc.Hadi A. 2006. Indonesia dan Problema. Jakarta : Tunggal Samudera.Karim Adiwarman A. 2010. Ekonomi Makro Islami .Edisi Kedua. Jakarta :PT Raja Grafindo Persada.-------------------------. 2007. Ekonomi Mikro Islami. Edisi Ketiga. Jakarta :PT Raja Grafindo Persada.Marius P. 1999. Dasar-Dasar Pemasaran. Cetakan Pertama. Jakarta.Mas’adi A. Ghufron. 2002. Fiqh Muamalah Konstektual. Jakarta: PT Raja Grafindo.Nanga, Muana. 2001. Makroekonomi:Teori, Masalah dan Kebijakan. Jakarta: : Raja Grafindo Persada.Payne, Adrian. 2000. Pemasaran Jasa . Yogyakarta : Penerbit Andi Yogyakarta. Pustaka LP3ES Indonesia. Raja Grafindo Persada.Rochim M . 2011. Bimbingan Umroh dan Haji Lengkap. Jakarta : Penerbit Erlangga.Sutar. 2006. Tuntunan Praktis Ibadah Haji dan Umroh. Surabaya : Penerbit dan Percetakan Offset Indah.